2016
DOI: 10.5018/economics-ejournal.ja.2016-11
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and Investment in the South and East Asia and Pacific Region: Evidence from Meta-Analysis

Abstract: The ability of any country to attract inward FDI is considered to depend on the quality of the economic governance found within that state. This study seeks to explore the value of quality economic governance in attracting FDI in South and East Asia by meta-synthesising 771 estimates from 48 empirical studies published between 1980 and 2012. The authors find evidence that countries with good quality regulation and low levels of corruption are able to attract more FDI. They also find that countries with stronge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…They also concluded that the institutional reforms should be given more consideration. Yerrabati and Hawkes (2016) performed a meta-analysis on the governance and FDI inflows relationship and reported that countries that have a low corruption level and good quality regulation get more FDI than other countries. Nguyen et al (2018) studied the institutional quality and economic growth nexus in 29 emerging economies and reported that positive association exist between the variables.…”
Section: Fdi-economic Growthmentioning
confidence: 99%
“…They also concluded that the institutional reforms should be given more consideration. Yerrabati and Hawkes (2016) performed a meta-analysis on the governance and FDI inflows relationship and reported that countries that have a low corruption level and good quality regulation get more FDI than other countries. Nguyen et al (2018) studied the institutional quality and economic growth nexus in 29 emerging economies and reported that positive association exist between the variables.…”
Section: Fdi-economic Growthmentioning
confidence: 99%
“…Hence, Bhutan must implement balanced regulation for maintaining the supply chain. The countries with good-quality regulation and low levels of corruption can attract more investment (Yerrabati and Hawkes, 2016). The imports are likely to stimulate the investment and can significantly decrease the current account deficit to 10.4% of GDP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite overwhelming evidence that political institutions play a key role in minimizing or exacerbating the influence of corruption (Yerrabati and Hawkes, 2016, Ferraz and Finan, 2011, Torsten et al, 1997, Myerson 1993 Ferraz and Finan (2011) opined that the predominant cross-country analysis of the role of political institutions on corruption has focused on macro-level analysis. As a result, this has impeded the unraveling of the full complement of political institutional architecture that promotes or inhibits corruption at country -industry or organizational levels.…”
Section: Theoretical Foundations: Institutions Corruption and Governancementioning
confidence: 99%